Reações estruturais, histoquímicas e fotossintéticas deGuapira opposita (Vell.) Reitz (Nyctaginaceae) àCecidomyiidae galhadores - Graziela Fleury Coelho de Araujo (2009)
Guapira opposita (Vell.) Reitz (Nyctaginaceae), a super-host of Cecidomyiidae(Schizomyiina) galls, is used as a model for evaluating the degree of different gallingherbivores potential for plants manipulation. Morphological, anatomical andhistochemical studies of four morphotypes induced by Bruggmannia elongata, B.robusta, Pisphondylia brasiliensis and an unidentified Cecidomyiidae aims to test ifphylogenetically related species induced galls with higher number of similarities relatedto shelter, protection and nutrition to the gall maker. The galls induced by Bruggmanniarobusta, B. elongata and the unidentified Cecidomyiidae presented the highest level ofsimilarities demonstrating that congeneric gall makers share the highest number ofcharacters when set in the same host plant. The gall of Pisphondylia brasiliensis showsthe most distinct phenotype when compared to the other three morphotypes because ofits larger number of unique characters. This gall, induced only in buds of G. opposita, issimilar to the bud galls described in literature, with shortening of internodes andextensive manipulation of the meristematic site, which end up with a high production ofleaf projections. These projections are generated from two patterns of meristematicactivity: the first one repeats apical pattern model in which crossed-opposite pairs ofleaves are generated, and the second from a meristem located at the base of each leafprojection, which gives rise to a new projection with its own axillary meristem.Differences in stem organogenic patterns and leaf projections production reflect the gallmakers ability to changing the course of apical meristem activity in its favor. In orderto verify whether the structure and photosynthetic capacity of the leaf projections aresimilar to the non galled leaf pattern, leaf anatomy, estimated stomatal conductance,pigment content and fluorescence of chlorophyll were analyzed in both materials. Theprojections, despite their small area, are anamtomically similar to the non galled leaves.The estimated stomatal conductance did not differ significantly, whereas chlorophyllscontent and the potential and effective quantum yields were reduced. We can concludethat the high density of projections may provide a compensatory increase in gallphotosynthesis, and so they can assist the maintenance of Pisphondylia brasiliensis -Guapira opposita system.